2016
DOI: 10.1161/circoutcomes.115.002603
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Surgery in Women

Abstract: S94S ex differences in outcomes have been noted in many areas of cardiovascular medicine. In mitral valve surgery, this topic is particularly important because in appropriately selected patients, mitral valve repair restores normal life expectancy, which cannot be said for other cardiac surgical operations. Current literature is replete with evidence supporting continued sex inequality in the detection and treatment of mitral valve disease. Women, although just as likely to have significant MR, are less likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 33 publications
2
30
1
2
Order By: Relevance
“…The etiology of this discrepancy in outcomes is still unclear with the following variables proposed—females are underrepresented in cardiovascular trials, present with VHD at an older age with more advanced disease, are with a worse preoperative risk profile, are referred for surgical intervention less often and/or later in the disease process, and are more likely to receive replacement than their male counterparts. 8 – 11,13,14,20,21,29,30,31 Therefore, determining whether the major risk factor for inferior outcomes following MV surgery is sex itself or the treatment that patients receive remains challenging. Large retrospective and prospective studies isolating for surgical approach, matching patients based on preoperative characteristics and comorbidities, and examining outcomes with long-term follow-up are required to elucidate this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of this discrepancy in outcomes is still unclear with the following variables proposed—females are underrepresented in cardiovascular trials, present with VHD at an older age with more advanced disease, are with a worse preoperative risk profile, are referred for surgical intervention less often and/or later in the disease process, and are more likely to receive replacement than their male counterparts. 8 – 11,13,14,20,21,29,30,31 Therefore, determining whether the major risk factor for inferior outcomes following MV surgery is sex itself or the treatment that patients receive remains challenging. Large retrospective and prospective studies isolating for surgical approach, matching patients based on preoperative characteristics and comorbidities, and examining outcomes with long-term follow-up are required to elucidate this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…5 Prior studies have hypothesized that differences in mitral valve morphology, complexity of lesions, timing of interventions, and comorbid conditions place female patients at a disadvantage at the time of surgery. 3 Although women are as likely to have significant mitral valve disease, they are less likely to receive surgery than male patients 6 and, when they do, operative mortality is higher among women undergoing mitral valve repair or replacement compared to men. 3 The purpose of this article was to identify preoperative, intraoperative, and postoperative risk factors for morbidity and mortality in a Brazilian female group of patients who underwent isolated mitral valve replacement, to obtain pertinent information regarding the current scenario in Brazil and contribute to a more gender-specific and individualized treatment of women.…”
Section: Discussionmentioning
confidence: 99%
“…12,15,17 On the other hand, participants of studies carried out in high-income countries are older, due to the predominance of degenerative and ischemic etiology of valve disease. 10,19 Studies have shown that mortality of cardiac surgery among women is higher than of their male counterparts, 3,5,6,11,[20][21][22] since women receive surgery late and usually have more severe preoperative conditions. 3,6,11,21,23 One of the possibilities for this fact is the use of cutoff points for echocardiographic variables without considering their body mass, which is generally lower than men's.…”
Section: Discussionmentioning
confidence: 99%
“…112 Similarly, in the presence of severe mitral regurgitation, delays in surgical intervention, and associated poorer outcomes can occur due to failure to index left ventricular enlargement to smaller body size of women. 113 Sudden cardiac death associated with mitral valve prolapse is more frequent in women with bileaflet prolapse, mitral annular disjunction, and frequent and repetitive premature ventricular contractions. 114,115 Mitral annulus calcification develops more often and more extensively in women and could lead rarely to degenerative mitral stenosis or regurgitation.…”
Section: Mitral Valve Diseasementioning
confidence: 99%